2015
DOI: 10.21608/jppp.2015.75384
|View full text |Cite
|
Sign up to set email alerts
|

TOXICITY AND BIOCHEMICAL EFFICACY OF NOVEL PESTICIDES AGAINST Aphis craccivora Koch (HEMIPTERA: APHIDIDAE) IN RELATION TO ENZYMES ACTIVITY

Abstract: Resistance development is a key part in pest management; Experimental trials included five conventional insecticides; Mospilan, Imidor (Neonicotinoid), Actellic (Organophosphate), Chess (Azomethine pyridines) and Aphox (Carbamate) to investigate their toxicity against both field and laboratory strains of Aphis craccivora Koch. The potency levels of the ongoing insecticides against the A. craccivora were 1.29, 1.43, 1.75, 1.97, 2.75 folds in laboratory strain more than that of field strain respectively. Thus, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…In our results for the preliminary toxicity evaluations of the solvents extract showed significant mortality of B. brassicae. Among the solvents extracts, methanol extract afforded high mortality which is in accordance with [28][29][30] who reported maximum mortality of Aphis craccivora by methanolic extract of C. colocynthis followed by ethyl acetate and petroleum ether extract. However, the activity of the crude extract can be attributed to the existence of specific chemical compounds of the plants like fatty acids (linoleic and oleic acid) glycosides (flavonoids, phenols, saponins), terpenoids and alkaloids, etc.…”
Section: Discussionsupporting
confidence: 85%
“…In our results for the preliminary toxicity evaluations of the solvents extract showed significant mortality of B. brassicae. Among the solvents extracts, methanol extract afforded high mortality which is in accordance with [28][29][30] who reported maximum mortality of Aphis craccivora by methanolic extract of C. colocynthis followed by ethyl acetate and petroleum ether extract. However, the activity of the crude extract can be attributed to the existence of specific chemical compounds of the plants like fatty acids (linoleic and oleic acid) glycosides (flavonoids, phenols, saponins), terpenoids and alkaloids, etc.…”
Section: Discussionsupporting
confidence: 85%
“…Esterase-mediated pesticide resistance has been detected in more than 30 insect pest species, according to (Hemingway et al, 1998). It was noted in our results that α -esterases activity and carboxylesterase decreased after thiamethoxam treatment which disagrees with (Shehawy and Alshehri, 2015) who discovered that imidacloprid treatment dramatically increased the α -esterases activities in a laboratory strain of cowpea aphid, also our results disagree with (Abdel-Haleem et al, 2020) who indicated that the third larval instar of Cx. pipiens treated with THIA showed a significant increase in the activity of the carboxylesterase and (α and β) esterases.…”
Section: Discussioncontrasting
confidence: 92%
“…Chemical insecticides are effective tools against this pest. However, the extensive use of chemical insecticides may cause such problems as mutation and carcinogenesis in non-target organisms or pest resistance [5]. Thus, it is very important to find other safer compounds that provide protection against pests without harmful effects to the non-target organisms.…”
Section: Introductionmentioning
confidence: 99%